2004
DOI: 10.1152/ajpgi.00253.2004
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-induced cell migration is mediated predominantly by the JAK-STAT pathway in primary esophageal keratinocytes

Abstract: The epidermal growth factor receptor (EGFR) activates several signaling cascades in response to epidermal growth factor stimulation. One of these signaling events involves tyrosine phosphorylation of signal transducer and activator of transcription (STAT), whereas another involves activation of the phosphatidylinositol 3-OH kinase pathway. Two possibilities for STAT activation exist: a janus kinase (JAK)-dependent and a JAK-independent mechanism. Herein, we demonstrate that EGFR overexpression in primary esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 36 publications
10
83
1
1
Order By: Relevance
“…In addition, EGFR signals can also induce JAK2 activation (18). Our results were compatible with these previous reports and implied that in various signaling pathways induced by leptin, EGFR transactivation acts upstream of both the JAK2 and ERK signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, EGFR signals can also induce JAK2 activation (18). Our results were compatible with these previous reports and implied that in various signaling pathways induced by leptin, EGFR transactivation acts upstream of both the JAK2 and ERK signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…The JAK/STAT signaling pathway has been extensively characterized in many systems, including hematopoietic, gastrointestinal, prostate, and vascular endothelial cells (2,4,5,17). In the context of cancers, JAK kinases can activate STATs, as well as many other signals, to promote cell survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with the processes of lens vesicle separation and lens epithelial/fiber cell differentiation that are disrupted in the Le-AP-2␣ mutant mice. Furthermore, stratification of these data into molecular function indicated that the majority of genes differentially regulated between normal and mutant lenses lacking AP-2␣ in the lens, reside in the epidermal growth factor receptor (Egfr) and Janus kinase (Jak) signal transduction cascades, pathways previously implicated in cell differentiation and cellular migration during development (Kumar and Moses, 2001;Andl et al, 2004;Brown et al, 2006).…”
Section: Microarray Analysis Of Ap-2␣-conditional Knockout Lenses Revmentioning
confidence: 99%